2014
DOI: 10.1530/rep-13-0580
|View full text |Cite
|
Sign up to set email alerts
|

Common fibroid-associated genes are differentially expressed in phenotypically dissimilar cell populations isolated from within human fibroids and myometrium

Abstract: Uterine fibroids are a prevalent gynaecological condition in reproductive-aged women and are the commonest reason for hysterectomy. The cellular composition of clonal fibroids are heterogeneous, with phenotypically dissimilar cells that include smooth muscle cells (SMC), vascular SMC (VSMC) and fibroblasts. The aim of our study was to investigate genes that are commonly differentially expressed between fibroid and myometrial whole tissues in phenotypically different sub-populations of cells isolated from fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
(78 reference statements)
1
7
0
Order By: Relevance
“…We detected ADM in patientmatched myometrial and leiomyoma tissue sections, although the expression varied (data not shown). Our results were consistent with reported discordant ADM expression found in other studies (58). Analysis of cells grown in culture showed a statistically significant decrease in ADM expression in hypoxic myometrium at 6 hours, and a >1.5-fold increase during hypoxia, when compared with normoxic myometrium (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…We detected ADM in patientmatched myometrial and leiomyoma tissue sections, although the expression varied (data not shown). Our results were consistent with reported discordant ADM expression found in other studies (58). Analysis of cells grown in culture showed a statistically significant decrease in ADM expression in hypoxic myometrium at 6 hours, and a >1.5-fold increase during hypoxia, when compared with normoxic myometrium (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Recent work by us and others have established that the cellular phenotypes of uterine fibroids are heterogeneous (Koumas et al 2001, Moore et al 2010, Zhao & Rogers 2013, Holdsworth-Carson et al 2014a. Studying the different cellular populations present within fibroids confirms the phenotypic plasticity of these cells and the dynamic nature of commonly used cell markers.…”
Section: Introductionmentioning
confidence: 66%
“…Myometrium from post-menopausal women exhibited increased ALDH1A1 expression. ALDH1A1 belongs to the retinoic acid (RA) pathway, which is known to be altered in fibroids (Catherino & Malik 2007, Zaitseva et al 2007, Holdsworth-Carson et al 2014a. Some RA pathway components are responsive to oestrogen, including cellular retinoic acid-binding protein 2 (CRABP2) (Li & Ong 2003), retinoid X receptor alpha (RXRα) and peroxisome proliferator-activated receptor gamma (PPARγ) (Tsibris et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Uterine leiomyomas are thought to originate from SMC in myometrium. However, recent studies have reported presence of fibroblasts and endothelial cells in uterine leiomyomas in addition to SMC populations 10,12 , thus suggesting presence of cellular heterogeneity in leiomyomas. We applied single cell RNA sequencing technique to create a cell atlas for the normal myometrium and the leiomyomas.…”
Section: Discussionmentioning
confidence: 99%
“…Leiomyomas are considered monoclonal tumors of smooth muscle cell in uterus 11 . However, recent histological and flow cytometry studies have shown the presence of smooth muscle cells, fibroblasts, endothelial cells and immune cells in leiomyomas 12 . How these cells contribute to the leiomyoma formation and the molecular salient characteristics of the cellular heterogeneity in leiomyomas remain undetermined.…”
Section: Introductionmentioning
confidence: 99%